To Be Authentic, to Be Eco: Exploring the Link Between Authenticity and Pro-environmental Behavior - Yang, Ying; Zhu, Shuhua; Gan, Yulu; Dang, Junhua (Frontiers in Psychology, 2021)
Authentic self is believed to be morally good. The current research proposes that the authentic self is also environmentally good. Across two studies, we tested the link between authenticity and pro-environmental attitude and behavior. In Study 1 (N=2,646), dispositional authenticity was found to be a predictor of pro-environmental behavior (PEB). In Study 2 (N=474), participants in the authentic condition (recalling their experiences of being authentic) were more willing to donate money to protect the environment than those in the inauthentic (recalling their experiences of being inauthentic) or the neutral (recalling their experiences of a typical day) conditions. Participants in the authentic condition also reported higher intention to conduct PEB than their peers in the other conditions. The results of the present research provide initial evidence that people are more likely to endorse pro-environmental attitude and behave pro-environmentally when being authentic.